需要利用积化和差公式∵ 2sinθ*[sinθ+sin3θ+...+sin((2n-1)θ)]=2sinθsinθ+2sinθsin3θ+.+2sinθsin[(2n-1)θ]=cos0-cos2θ+cos2θ-cos4θ+cos4θ-cos6θ+.+cos(2n-2θ)-cos(2nθ)=cos0-cos(2nθ)=1-cos(2nθ)...
求证sinθ+sin3θ+...+sin((2n-1)θ)=sin^2(nθ)/sinθ
3个回答
相关问题
-
求证sinθ/(1+cosθ)+(1+cosθ)/sinθ=2/sinθ
-
求证:(1+cosθ+cosθ/2) /(sinθ+sinθ/2)=sinθ/1-cosθ
-
求证 (sinθ+cosθ-1)(sinθ-cosθ+1)) /sin2θ=tanθ/2
-
:求证:(1-2sinθcosθ)/(cos2θ-sin2θ)=(cos2θ-sin2θ)/(1+2sinθcosθ).
-
求证:sin2θ+sinθ/2cos2θ+2sin^2θ+cosθ=tanθ
-
求证:tanθ*sinθ/tanθ-sinθ=1+cosθ/sinθ
-
sin^2θ/sinθ-cosθ + cosθ/1-tanθ = sin^2θ/sinθ-cosθ + cosθ/1-(
-
求证sinθ-cosθ+1/sinθ+cosθ-1=1+sinθ/cosθ
-
lim(cos^nθ-sin^nθ)/(cos^nθ+sin^nθ)
-
试证:tanθ(1+sinθ)+sinθtanθ(1+sinθ)−sinθ=[tanθ+sinθ/tanθsinθ].